Trunk-pelvis coordination during load carriage running. (26th August 2020) - Liew, Bernard X.W.; Morris, Susan; Netto, Kevin
Abstract: Understanding the influence of load carriage on trunk-pelvis coordination and its variability has important functional implications for athletes who need to run with load. The aim of this study was to examine the influence of load carriage on trunk-pelvis coordination in running. Thirty healthy adults performed running while wearing a 20% bodyweight backpack, and without load. Vector coding was used to quantify trunk-pelvis segmental coordination and its variability during the stance phase of running. The four coordination patterns were: 1) anti-phase (segments moving in opposite directions), in-phase (segments moving in same directions), trunk-only phase (only trunk movement), and pelvic-only phase (only pelvic movement). For each plane, the percentage of stance phase spent in a specific coordination pattern was quantified. Coordination variability for each plane was averaged over the stance phase. Mixed effects models were used to analyse the effects of load, adjusted for the covariate of sex, on coordination and its variability. Running with load increased trunk-only coordination in the sagittal plane (P < 0.001), increased anti-phase coordination in the frontal plane (P < 0.001), reduced trunk-only phase coordination in axial rotation (P < 0.001), and increased coordination variability in all three planes (Flexion-Extension: P < 0.001; Lateral flexion: P = 0.03; Axial rotation: P < 0.001). Future studies would benefit from investigating how trunk-pelvis coordination and its variability alters candidate end-point variability indices (e.g. COM displacement), and its functional implications in load carriage running.